Assessment of Pain Perception of Aesthetic Procedures During Menstrual Period in Comparison to Non- Menstrual Period days - Bin Rubaian NF; AlGhamdi NJ; AlHemli HA; AlHuraish DS; Bukhari AE; Amir BA (International Journal of Women's Health)
Nouf F Bin Rubaian,1 Nada J AlGhamdi,1 Haya A AlHemli,2 Deemah S AlHuraish,2 Abrar E Bukhari,3 Baraa A Amir2 1Imam Abdulrahman Bin Faisal University, Department of Dermatology, King Fahad Hospital of the University, Al Khobar, Saudi Arabia; 2College of Medicine, Imam Abdulrahman bin Faisal University, Dammam, Eastern Province, Saudi Arabia; 3Department of Dermatology, College of Medicine, Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi ArabiaCorrespondence: Deemah S AlHuraish, Email Deemahalhuraish@gmail.comPurpose: A global survey conducted by The International Society of Aesthetic Plastic Surgery (ISAPS) in 2022 reported 18.8 million non-surgical cosmetic procedures, with women representing 87%. Recent literature has shined a light on the possible implication of female sex hormones on the perception of pain, but the influence of these hormones on pain perception secondary to aesthetic procedures have scarcely been studied. Our study aimed to investigate the influence of the menstrual cycle on pain perception during non-surgical aesthetic procedures. The study explored the correlation between different phases of the menstrual cycle, the presence of premenstrual symptoms, and the severity of pain experienced by participants.Patients and Methods: A questionnaire-based cross-sectional study was conducted at dermatology clinics in Saudi Arabia. 383 complete responses were collected from participants who provided data on demographic factors, aesthetic procedures, menstrual status, premenstrual symptoms, and pain severity.Results: The 383 participants reported that the most frequent procedures were laser hair removal (82.5%) and injectables. Pain perception was highest for laser hair removal across all menstrual phases (4.5± 2.66, 4.8± 3.06 and 4.3± 3.48), and lowest for Ultherapy (1.56± 1.66, 1.40± 1.36 and 1.37± 1.37). Significant positive correlations were found between premenstrual symptom severity and pain perception in laser hair removal and injectables. Linear regression analysis revealed a significant negative association between age and pain perception in laser hair removal, while age had a positive association with other procedures.Conclusion: In conclusion, pain perception during non-surgical aesthetic procedures varies across menstrual phases and is influenced by the type of procedure. The negative relationship between age and pain in laser hair removal requires further research. These findings can help practitioners better manage patient expectations and experiences during these cosmetic treatments.Keywords: non-surgical aesthetic procedures, laser hair removal, injectables, menstruation